Design of a Soybean Washing Machine to Increase Productivity in the Tempe Production Process - Inayah Aulia Nursyabani; Siti Muhimatul Khoiroh (Yayasan Inovasi Kemajuan Intelektual, 2026)
This study aims to design an ergonomic soybean washing machine to improve the efficiency and productivity of the tempeh production process at UD. XYZ. The main problem faced by the company is the low capacity of soybean washing which is still done manually, causing delays in the production flow and becoming a bottleneck in the production system. The study was conducted with an ergonomic approach through anthropometric measurements of operators as a basis for designing the machine to suit user needs and provide work comfort. The anthropometric data obtained were then tested using adequacy tests and data uniformity tests to ensure the validity and feasibility of the data. The machine design is based on the 95th percentile so that it can be used by most operators. In addition, the study also used the POSPAC method to analyze productivity levels before and after the implementation of the soybean washing machine. The research results show that the anthropometric data meets the requirements of adequacy and uniformity, making it suitable for use as a design reference. The designed machine can increase soybean washing capacity from 25 kg to 50 kg in a single process, significantly improving production efficiency and smoothness. Productivity analysis shows an increase in most productivity indicators, although capital productivity decreased due to the initial investment in machine procurement. Furthermore, production capacity has increased to meet and even exceed market demand. Thus, the ergonomic design of the soybean washing machine has proven effective in improving the performance and productivity of the tempeh production system at UD. XYZ.